Analysis of compression/release stabilized transfemoral prosthetic socket by finite element modelling method. (September 2020) - Meng, Zhaojian; Wong, Duo Wai-Chi; Zhang, Ming; Leung, Aaron Kam-Lun
Highlights: The study evaluated residual limb fitted with compression/release stabilized socket The socket was designed base on 3D reconstructed geometry of magnetic resonance image Stress tended to concentrate in the proximal region of compression areas Maximum stress and contact pressure were larger than conventional socket condition Abstract: The aim of this study was to investigate the residual limb stress of a transfemoral amputee's Compression/Release Stabilized (CRS) socket by finite elemental modelling. The model was constructed from magnetic resonance images of the left residual limb of a 48-year-old male transfemoral amputee. Two conditions were simulated. In the donning condition, the prosthetic socket under the residual limb moved proximally until it reached the required donned position. The weight-bearing condition was subsequently simulated by applying body weight (800N) at the femoral head while keeping the distal end of the socket fixed. The maximum contact pressure was concentrated at the proximal anterior-medial regions of the residual limb surfaces in both conditions. In the donning condition, the maximum von Mises stress and the maximum contact pressure were 277.7 kPa and 254 kPa respectively. The respective values were 191.9 kPa and 218.5 kPa when body weight was applied. The stress and contact pressure did not exceed the suggested threshold value of pain. Our findings provide important biomechanical information on the CRS socket that may help future design optimization.